The Relationship Between Mathematical Literacy and Early Childhood's Habits of Mind - Dalimunthe, Efrida Mandasari; Raisatunnisa, Raisatunnisa; Siregar, Agung Kaisar (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Mathematical literacy supports the importance of children developing a strong understanding of basic mathematical concepts and engaging in mathematical explorations that are relevant to their lives. Mathematical literacy refers to a child's ability to understand and apply basic mathematical concepts, while habits of mind include deep thinking habits such as critical, creative, and reflective thinking. This study aims to explore the relationship between mathematical literacy and habits of mind in early childhood. This study used a quantitative approach with a correlational design, involving 28 preschool children selected through stratified cluster sampling. Data were collected using a mathematical literacy test, a habits of mind questionnaire, and interviews with parents and teachers. The results showed that there was a significant positive relationship between mathematical literacy and habits of mind (r = 0.730, p < 0.05). The contribution of habits of mind to mathematical literacy was 53.3%, indicating that good habits of mind play an important role in improving children's mathematical literacy. So it can be concluded that developing habits of mind through well-planned learning can strengthen early childhood mathematical literacy.